Development and Evaluation of a Peer Mentorship Program for Aboriginal University Students - Rawana, Jennine S.; Sieukaran, Daniella D.; Nguyen, Hien T.; Pitawanakwat, Randy (Canadian journal of education, 2015)
Although Aboriginal students encounter educational challenges, few post-secondary mentorship programs that facilitate positive educational and mental health outcomes within this population are described in the literature. This study describes the development and evaluation of a mentorship program for Aboriginal university students. Program development was informed by a literature review and needs assessment. Using a mixed-methods design, 12 Aboriginal students completed pre- and post-program measures of resilience and ethnic identity awareness. Post-program, improvements in social competence resiliency, other-group ethnic orientation, and school engagement were identified. Research and community stakeholders are encouraged to develop mentorship programs to improve the well-being of Aboriginal students.